Building connections: co-creation experiences as an affective branding strategy in children's fashion (ModaPalavra e-periódico, 2026)
This article aims to understand how consumer content co-creation contributes to emotional engagement, a sense of belonging, and the symbolic strengthening of a brand. The research, of a qualitative and descriptive nature, was conducted with 14 families who participated in photographic campaigns promoted by the brand LOK, in which parents were invited to create original images of their children wearing apparel from the new collection. The responses were analyzed in light of theoretical frameworks on branding, brand experience, identification, co-creation, and consumer behavior. The results suggest that participants felt free to create and emotionally connected to the brand, and that co-creation functioned as a catalyst for symbolic bond and loyalty. The study also highlights the potential of collaborative strategies for small fashion brands. Finally, the study outlines its limitations and suggests directions for future research.
Keywords: branding; co-creation; brand experience; children's fashion; consumer engagement